PENGARUH LATIHAN CONE DRILL (START DRILL, SPRINT, BACKPEDAL, SHUFFLE) TERHADAP KELINCAHAN TIM BASKET SMPN 29 PEKANBARU - Putra, Nanda Andrika; ', Slamet; agust, Kristi agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on my observation time of the trial against SMPN 6 Pekanbaru, the authors conclude that there is still a lack of agility on the player's basketball team SMP 29 Pekanbaru, the deficiency is seen when chasing balls in passing by the center, the player can not catch up, and the lack of ability to steal the ball and chase your opponent, what happens when the basketball team lost ball SMP 29 Pekanbaru very less agility to get back to defense. The purpose of this study was to look at the effects of exercise cone drill (drill star, sprint, backpedal, shuffle) on the basketball team agility SMP 29 Pekanbaru. As the population used in this study is the basketball team SMP 29 Pekanbaru totaling 10 people. In this study a total population of 10 people (sampling saturated). According Sugiyono (2013: 124-125) saturation sampling is sampling technique when all members of the population used as a sample. The instrument used to collect data that test agility with Pree and post test illinois agility test run. The data obtained was analyzed using t-test. T test results can be seen that t for 10,037> 1,833 (t-tables) and then Ho is rejected and Ha accepted, meaning there are the effects of exercise "cone drill (start drill, sprint, backpedal, shuffle) to the agility of a basketball team SMP 29 Pekanbaru , When viewed from the difference in the average number agility between Pree-test and post-test at 2:43, shows that exercising "cone drill (start drill, sprint, backpedal, shuffle) to agility provide a better change at 13:58% compared before given exercise.